Gerschenkron Redux? Analysing new evidence on joint-stock enterprise in pre-War Shanghai - Niv, Horesh (Wiley, 2015)
Alexander Gerschenkron (1904–78) famously postulated that the more backward an economy was at the outset of industrialisation, the more reliant it would be on state-backed banks as a means of directing investment. Gerschenkron thereby implied that impersonal equity markets were likely to play a less significant role in countries aiming to catch up with the west. This article is aimed at examining Gerschenkron’s thesis primarily through an analysis of shareholding in 1930s Shanghai. Drawing on newly discovered archival material as well as on recent studies, the paper clarifies the magnitude of joint-stock enterprise and the ubiquity of stockexchange trade in a city that was by far China’s most important economic hub. The pattern of joint-stock enterprise in pre-war China is compared with that of Japan, the first non-Western society to become fully industrialised. The argument advanced is that Gerschenkron’s thesis incorrectly played down the significance of impersonal equity markets to pre-war Japan’s successful industrialisation and to the limited nature of pre-war China’s industrialisation. Japan could sustain its industrialisation thrust in the early 20th century on a nation-wide scale partly because of the growing vitality of its equity markets in Tokyo and Osaka. By contrast, China’s pre-war industrialisation was much less extensive because its equity markets were more limited.